Automation and Selection Technique for Regression Testing: An Empirical Analysis - Hilman, Muhammad; Mantiri, Wulan (AI Society & STMIK Indonesia, 2025)
Software testing, particularly regression testing, is a process that is required when changes are made to the software or its environment to ensure that the software continues to perform as expected. Motivated by real industry needs, this study reports on the experience of transitioning from manual to automated regression testing in one of the mobile applications at PT. XYZ. Prior to this study, regression testing was conducted manually, resulting in significant costs and inherent subjectivity. Test automation is then applied to the activities of test execution and test result integration as an effort to increase test productivity and efficiency. This study aims to find an efficient testing alternative by separating the flow that runs tests related to changes from the flow that runs all tests. Based on the analysis of the tested application, each flow has its trade-offs. The results show that test automation can provide benefits for regression testing, application releases, and software engineering flow. The framework presented in this paper aims to serve as a guideline for other industrial applications with similar specifications that are also considering implementing test automation.